Communication Apprehension among ESL College Learners - Carin, Nova Ness Fabrienne (International Journal of Multidisciplinary: Applied Business and Education Research, 2025)
Language learners often encounter challenges when speaking a non-native language, such as English as a Second Language (ESL). These difficulties can arise not only from the complexity of language skills but also due to anxiety. This study investigated language anxiety, spe-cifically communication apprehension, among freshmen college stu-dents enrolled in a basic communication course. Quantitative and qualitative methods were employed, including a survey questionnaire and focus group discussions. The findings indicate that a majority of students experience average levels of communication apprehension. Notably, females exhibited higher communication apprehension compared to males. These results suggest that language anxiety, par-ticularly communication apprehension, may be influenced by expo-sure to language use and the classroom environment.